Current status and correlation analysis of occupational commitment and job burnout in nurses - Mao Li; Ding Yangyang; Cao Kunming; Li Zhengfa (Sichuan jingshen weisheng, 2021)
ObjectiveTo analyze the current status and correlation of occupational commitment and job burnout in nurses.MethodsOccupational commitment scale and Maslach Burnout Inventory General Survey （MBI-GS） were used to survey 695 nurses in 4 hospitals in Nanchong， and the assessment results were compared among nurses with different demographic characteristics， thereafter， Pearson correlation analysis was conducted to discuss the correlation between occupational commitment and job burnout in nurses.ResultsThe total scores of occupational commitment scale and MBI-GS of nurses were （78.38±12.33） and （37.05±9.61）， respectively. The total occupational commitment scale score showed significant differences among nurses of different hospitals， departments， working years and genders （P<0.05 or 0.01）， and the total MBI-GS score showed statistical differences among nurses of different hospitals， departments， ages， professional titles， working years， educational level and marital status （P<0.05 or 0.01）. Pearson correlation analysis showed that the total score and each dimension score of MBI-GS were negatively correlated with the total score of occupational commitment scale， as well as the scores of affective commitment， normative commitment and economic cost commitment （r=-0.517~-0.075，P<0.05 or 0.01）. The emotional cost commitment score was negatively correlated with the the total MBI-GS score， along with the scores in professional efficacy and depersonalization dimensions （r=-0.172~-0.098， P<0.01）. The score of opportunity commitment was positively correlated with the score of professional efficacy （r=0.106， P<0.01）， and negatively correlated with the score of emotional exhaustion and depersonalization （r=-0.156， -0.123， P<0.01）.ConclusionThe hospital， department and working years of the nurses are the common factors influencing occupational commitment and job burnout. The occupational commitment is higher in female nurses than that in male nurses， and the job burnout is more severe in the unmarried than that in the married， moreover， the job burnout of the nurses is negatively correlated with occupational commitment.